2022
DOI: 10.3389/fped.2022.867968
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers' Attitudes Toward COVID-19 Vaccination in Children and Adolescents With a History of SARS-CoV-2 Infection

Abstract: BackgroundLimited data are available on the attitudes of caregivers toward COVID-19 vaccination in children and adolescents with a history of SARS-CoV-2 infection or Long Covid symptoms. The aim of this study was to investigate the vaccine hesitancy among caregivers of children and adolescents with a documented history of SARS-CoV-2 infection and to explore the possible associations between COVID-19 manifestations and the acceptance of the vaccine.MethodsCaregivers of children or adolescents with a microbiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…The most common predisposing factor for VH found in the included studies and related to vaccination is the fear of developing adverse reactions [ 19 , 23 , 24 , 25 , 29 , 34 , 37 , 38 , 39 , 43 , 45 , 49 ]. Another significant aspect is the distrust or doubts about vaccination against COVID-19 and its efficacy [ 20 , 21 , 24 , 27 , 34 , 38 , 44 , 49 , 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most common predisposing factor for VH found in the included studies and related to vaccination is the fear of developing adverse reactions [ 19 , 23 , 24 , 25 , 29 , 34 , 37 , 38 , 39 , 43 , 45 , 49 ]. Another significant aspect is the distrust or doubts about vaccination against COVID-19 and its efficacy [ 20 , 21 , 24 , 27 , 34 , 38 , 44 , 49 , 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…None of the cases reported in literature required intensive care support, thus suggesting a potential protection against life-threatening MIS-C in vaccinated people ( 6 , 20 ). The low incidence of MIS-C in vaccinated people, together with the reduced spectrum of severity observed significantly support the utility of anti-SARS-CoV-2 vaccination in children and adolescents, although vaccine hesitancy among caregivers is still consistent ( 21 ). As the clinical phenotype that we reported in our patient presents peculiar findings, including the prominent hepatic and pancreatic involvement [described in few MIS-C patients ( 4 )] and the absence of a significant cardiovascular impairment, it is possible to hypothesize that the different immunologic background of vaccinated patients could also influence the clinical phenotype of MIS-C. To this regard, the different kinetic of the pulmonary and hepato-pancreatic picture in response to IVIG could be attributed to the secondary activation of the adaptive immunity following the initial cytokine release by innate immune cells.…”
Section: Discussionmentioning
confidence: 89%
“…Other children’s vaccination status may represent an important determinant of parental acceptability for their younger children. Third, the history of COVID-19 infection was not collected in our surveys, and an Italian study showed that parents with children previously experiencing COVID-19 were more likely to support the vaccination [ 55 ]. However, as the daily confirmed cases were very low during the two surveys due to the zero COVID policy in China, the COVID-19 infection history would not substantially influence the results.…”
Section: Discussionmentioning
confidence: 99%